Pengaruh Media Pembelajaran dan Minat Belajar Siswa terhadap Penguasaan Konsep Ilmu Pengetahuan Alam - Janatin Janatin (Journal Innovation In Education, 2024)
This study aimed to investigate the influence of learning media and learning interest on the mastery of Science concepts among fifth-grade elementary school students. Data were collected from 60 students divided into four treatment groups, including interactive and conventional learning media, as well as high and low learning interest. Data analysis employed statistical tests, including tests for normality, homogeneity, and hypotheses. The results indicated that both learning media and students' learning interest significantly influenced the mastery of Science concepts. Interactive learning media and high learning interest had a significant impact on Science concept mastery, with respective significance values of 0.019 and 0.003. However, the interaction between learning media and students' learning interest did not significantly affect Science concept mastery. In conclusion, this study underscores the importance of learning media and learning interest in enhancing students' understanding of Science concepts. The implications of these findings can be utilized to develop more effective learning strategies to improve Science concept mastery in elementary schools.